Cancer care near the end‐of‐life in Austria: A retrospective data analysis. (7th February 2021) - Robausch, Martin; Grössmann, Nicole; Wild, Claudia
Abstract: Objective: Since end‐of‐life care (EOL) is an internationally accepted indicator for the quality of oncological care we aimed to investigate the current EOL care situation for Austrian cancer patients especially concerning the place of death cancer treatment hospitalisation near death and palliative care. Methods: A retrospective data analysis was carried out based on Austrian routine inpatient data of the years 2012 to 2016. Data including the date of death of adult patients with a main hospital discharge diagnosis of a neoplasm were included. All analyses were source‐related and based on the place of residence. Results: In total 80818 cancer patients have died between 2012 and 2016 of whom 53.4% died in the inpatient setting. Palliative care at the EOL (last hospitalisation) was present in 12.9% of patients whereby more than 50% were admitted two to 14 days before death. Considering cancer treatment at the EOL (30 days before death) 6.9% of cancer patients have received chemotherapy 1.7% radiation therapy and 0.75% were treated with a monoclonal antibody. Conclusion: In international comparison Austria appears to do well on quality indicators concerning ICU‐admission and chemotherapy treatment average on hospital death and poorly on hospital admissions and timely referral for palliative care.